Programa de Gestão e Desempenho: implementação, desafios e efeitos na percepção dos servidores e gestores da UFSCar – Campus Araras - Peres, Maiara Fernanda (2025)
The social distancing measures imposed by the COVID-19 pandemic have significantly transformed the dynamics of working practices. Faced with this pandemic scenario, the Federal University of São Carlos (UFSCar) adopted teleworking to ensure the continuity of its activities. In 2022, UFSCar implemented the Management and Performance Program (PGD), which regulated this change, transforming the logic of the services provided. This research aims to analyze the perceptions of civil servants at the Federal University of São Carlos (UFSCar), Araras campus, about the Management and Performance Program (PGD). The analysis included both employees participating and not participating in the program, as well as the managers responsible for monitoring deliveries, considering the diversity of activities carried out at the University. To this end, a mixed approach was adopted, combining qualitative methods, which explored the perceptions of individuals, and quantitative methods, which allowed patterns and trends to be analyzed. The research also included participant observation, providing a broader understanding of the context studied. The results obtained provide support for improving the DMP, helping to ensure that organizational transformations meet institutional demands and promote the continuous improvement of public services.